Analysis of Power Efficiency Produced by AC and DC Generators: A Literature Review - Deddy Supriyatna (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
In the life of the modern era, electricity has become one of the supporters of the energy supply to meet all of human's daily needs. Electricity can be generated from the conversion of natural energy such as sunlight, wind, coal and so on. Generators have become modern renewal machines that can convert mechanical energy into electrical energy. Generator with a work system that utilizes wire coils as a conductor of electricity and the stator and rotor work continuously to convert motion energy into electrical energy. This study aims to answer the problem regarding the efficiency between the two types of AC and DC dynamos. As well as to find out which type of dynamo is suitable for a particular electrical component. The data collection technique was carried out using a System Literature Review (SLR) which was used to identify and study theoretically the power efficiency generated by AC and DC generator dynamos. Dalam kehidupan era modern, listrik telah menjadi salah satu penyokong suplai energi untuk memenuhi semua kebutuhan manusia sehari-hari. Listrik bisa dihasilkan dari konversi energi alam seperti cahaya matahari, angin, batu bara dan sebagainya. Generator telah menjadi mesin pembaruan modern yang dapat mengubah energi mekanik menjadi energi listrik. Generator dengan sistem kerja yang memanfaatkan lilitan kawat sebagai penghantar listrik dan stator serta rotor yang bekerja terus menerus untuk mengkonversi energi gerak menjadi energi listrik. Penelitian ini bertujuan untuk menjawab permasalahan menngenai efisiensi antara kedua jenis dinamo AC dan DC. Serta untuk mengetahui dinamo tipe mana yang cocok untuk sebuah komponen listrik tertentu. Teknik pengumpulan data dilakukan dengan System Literature Review (SLR) yang digunakan untuk mengidentifikasi serta mengkaji secara teori mengenai efisiensi daya yang dihasilkan dinamo generator AC dan DC.